Implementation of the IDEAL method in developing mentoring skills among PPG prospective teachers - Fathul Anwariyah; Thitra Padma Rani; Ani Nurdiana (CV. SPDFHarmony, 2025)
Background: Mentoring plays a critical role in supporting the professional development of prospective teachers during teacher professional education programs. In the context of the Indonesian Teacher Professional Education Program (PPG), mentoring practices often face challenges related to diverse academic backgrounds, particularly between graduates of teacher education and subject-matter disciplines. These conditions require a structured and reflective mentoring approach that can bridge pedagogical knowledge, content mastery, and classroom practice.Aims: This study aims to examine the implementation of the IDEAL method in developing mentoring skills among mathematics PPG prospective teachers during the teaching practicum.Methods: This study employed a qualitative descriptive approach with a reflective practice design. The participants were mathematics PPG prospective teachers undertaking their teaching practicum at a partner secondary school. Data were collected through classroom observations, reflective dialogues, and document analysis. The research procedure was structured according to the five stages of the IDEAL method: Identification, Listening, Exploration, Action, and Lesson (Reflection). Data were analyzed using reflective thematic analysis.Result: The findings indicate that the IDEAL method facilitated a structured and reflective mentoring process that accommodated differences in academic backgrounds, strengthened pedagogical awareness, and enhanced professional confidence. Each stage of the IDEAL method supported prospective teachers in integrating pedagogical knowledge, content understanding, and reflective practice within authentic classroom contexts.Conclusion: The study concludes that the IDEAL method provides an effective mentoring framework for supporting the professional development of mathematics PPG prospective teachers. By emphasizing dialogical interaction, experiential learning, and sustained reflection, IDEAL-based mentoring contributes to the development of mentoring skills and reflective professional identity during the teaching practicum.